Examination of the U.S. Air Force's aircraft sustainment needs in the future and its strategy to meet those needs (National Academies Press, 2011)
The ability of the United States Air Force (USAF) to keep its aircraft operating at an acceptable operational tempo, in wartime and in peacetime, has been important to the Air Force since its inception. This is a much larger issue for the Air Force today, having effectively been at war for 20 years, with its aircraft becoming increasingly more expensive to operate and maintain and with military budgets certain to further decrease. The enormously complex Air Force weapon system sustainment enterprise is currently constrained on many sides by laws, policies, regulations and procedures, relationships, and organizational issues emanating from Congress, the Department of Defense (DoD), and the Air Force itself. Against the back-drop of these stark realities, the Air Force requested the National Research Council (NRC) of the National Academies, under the auspices of the Air Force Studies Board to conduct an in-depth assessment of current and future Air Force weapon system sustainment initiatives and recommended future courses of action for consideration by the Air Force.